Nanoscience and Engineering in Superconductivity - Moshchalkov, Victor; Woerdenweber, Roger; Lang, Wolfgang (NanoScience and Technology, 2010)
For emerging energy saving technologies superconducting materials with superior performance are needed. Such materials can be developed by manipulating the "elementary building blocks" through nanostructuring. For superconductivity the "elementary blocks" are Cooper pair and fluxon (vortex). This book presents new ways how to modify superconductivity and vortex matter through nanostructuring and the use of nanoscale magnetic templates. The basic nano-effects, vortex and vortex-antivortex patterns, vortex dynamics, Josephson phenomena, critical currents, and interplay between superconductivity and ferromagnetism at the nanoscale are discussed. Potential applications of nanostructured superconductors are also presented in the book.